Sedentary behavior in patients with knee osteoarthritis before and after total knee arthroplasty: A systematic review - Frimpong, E.; McVeigh, Joanne; Meiring, R. (Human Kinetics Inc, 2018)
Objective: The objective of this systematic review is to integrate the available evidence on changes in sedentary behavior (SB) in patients with knee osteoarthritis after total knee arthroplasty (TKA). Methods: A systematic literature search from January 2002 to October 31, 2017, was performed for studies assessing objectively and/or subjectively measured SB following TKA. The Scottish Intercollegiate Guidelines Network Methodology appraisal tool was used to critically appraise the methodological quality of the included studies. Results: Ten studies reporting on SB with a total of 1,028 participants were included in the review. Three studies reported changes in SB with two showing a reduction in SB and one (with high risk of bias) an increase in SB after TKA. Seven studies showed no change in SB following TKA. Conclusion: Currently, there is insufficient evidence which suggests that SB time improves following TKA. Detailed assessments of SB after TKA are needed.